The state of Pauline studies : a survey of recent research - Gupta, Nijay K.; Heim, Erin M.; McKnight, Scot (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2024)
"A diverse team of leading scholars survey the current landscape of Pauline studies, offering readers a concise guide to contemporary discussions"--
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc. -- History -- 21st century